The prognostic influence of tumor infiltrating Foxp3+CD4+, CD4+ and CD8+ T cells in resected non-small cell lung cancer. Issue 1 (December 2015) - Jackute, Jurgita; Zemaitis, Marius; Pranys, Darius; Sitkauskiene, Brigita; Miliauskas, Skaidrius; Bajoriunas, Vytis; Lavinskiene, Simona; Sakalauskas, Raimundas
Abstract Background Different subsets of tumor infiltrating T lymphocytes are believed to play essential role in the immune response to cancer cells. The data of these cells in NSCLC are relatively rare and controversial therefore we aimed to evaluate the infiltration patterns of Foxp3 + CD4+, CD4+ and CD8+ T cells in NSCLC and to analyze their relations to survival. Methods Lung tissue specimens from 80 newly diagnosed and untreated patients who underwent surgery for NSCLC (stages I-III), and 16 control group subjects, who underwent surgery due to recurrent spontaneous pneumothorax, were analyzed. Foxp3 + CD4+, CD4+ and CD8+ T cells in tumor stroma and islets were evaluated immunohistochemically. All statistical analyses were performed using the Statistical Package for the Social Sciences (SPSS), version 20.0. Results Tumor infiltrating CD4+, CD8+ T cells were associated with neither overall survival nor disease-free survival. The presence of high tumor stroma infiltrating Foxp3 + CD4+ T cells was independently associated with improved NSCLC patients overall survival (P  < 0.05). Conclusions Our study demonstrated that tumor infiltrating Foxp3 + CD4+ T cells are associated with improved NSCLC patients' survival. In addition our findings highlight a tendency of high CD4+/CD8+ and CD8+/Foxp3 + CD4+ T cells ratio in prolonged NSCLC patients' survival.